Epidemiological and Diagnostic Study of Cutaneous Leishmaniasis at Kut City - Altaj, Ali H. Abd; A. Rahi, Abdulsada (American Journal of Biology and Natural Sciences, 2025)
This study is an epidemiological and diagnostic study of cutaneous leishmaniasis (CL), in Kut city, Iraq, during November, 2024- April, 2025 . Sixty nine suspicious cases were analyzed using Giemsa-stained skin smears whereby, 36 cases (52.2 %) of them were positive. The results showed that the group that was mostly affected was children that aged (1 -10) years old, and it could be either because of behavioral or immunological reasons. Even though higher infection rate among the girls was observed, the sex-difference was not always statistically significant and this fact proves that further research on sex-related susceptibility should be done. Residency wise, the cases were slightly higher in the rural than the urban setting indicating that the environmental and socioeconomic settings could have a contribution in the spreading of the disease. Regarding the type of lesion, the wet and dry forms of CL were found to have the same rate of infection among the confirmed cases. The findings support the significance of reinforcement in health education and awareness particularly in children and rural setting to manage and cut down CL burden in endemic regions.